Analisis Pengaruh Kompleksitas Perusahaan, Profitabilitas dan ukuran Perusahaan terhadap Audit Delay - Indiana, Firdha; ., Triandi (Jurnal Ilmiah Akuntansi Kesatuan, 2017)
Timeliness in financial reporting is an obligation for companies listed in the Indonesia Stock Exchange to submit periodic financial reports. Delay in financial reporting will have a negative effect on a company, because it may indicate the existence of financial problem within the company. The length of time of an audit conducted by an auditor can be seen from the time difference between the financial statement date and the date the auditor’s report was signed in the financial statement. The time difference is often called an audit delay or audit report lag. The longer the auditor completes the audit, the longer the delay is. If the audit delay is long, the delay in submitting financial statement to stakeholders will be longer. Prompt financial reporting is essential to maintain the accuracy of information presented in the financial statement. According to previous studies, there are many factors affecting audit delay, including company’s complexity, auditor’s opinion, reputation of public accounting firm, solvability or leverage, profitability, and company’s size. This motivates the author to identify what factors affect audit delay and whether the factors known from previous studies remain consistent. This study aims to analyze the effect of company’s complexity, profitability, and company’s size on audit delay in manufacturing companies in Indonesia Stock Exchange in 2012 and 2013. The data sample is taken from 102 companies. The method of analysis used is multiple linear regression analysis, which is preceded by the classical assumption test, namely normality test, heteroscedasticity test, multicollinearity test, and autocorrelation test. The result gathered from the manufacturing companies listed on Indonesia Stock Exchange in 2012 and 2013 show that, in partially conducted tests, company’s complexity has no effect on audit delay. Profitability has an effect on audit delay. Company’s size however, has an effect on audit delay. On the other hand, from simultaneously conducted test, it is known that company’s complexity, profitability, and company’s size have simultaneous effect on audit delay.